126k views
5 votes
Find the 10th term of the following sequences T(2)=20 and the term-to-term rule is subtract 6​

User Wam
by
5.4k points

2 Answers

2 votes

Answer:

-28.

Explanation:

T(1) = 20 + 6 = 26.

This is an arithmetic series with:

nth term T(n) = 26 - 6(n - 1).

So T(10) = 26 - 6(10-1)

= 26 -54

= -28.

User JVS
by
5.8k points
7 votes

Answer is -28

==================================================

Work Shown:

T(2) = 20 means the second term is 20

T(1) = 26 because we go backwards from what the rule says (subtract 6) to step back one term. Going forward, 26-6 = 20.

Since a = 26 is the first term and d = -6 is the common difference, the nth term is

T(n) = a + d*(n-1)

T(n) = 26 + (-6)(n-1)

T(n) = 26 - 6n + 6

T(n) = -6n + 32

Plugging n = 1 into the equation above leads to T(1) = 26. Using n = 2 leads to T(2) = 20.

Plug in n = 10 to find the tenth term

T(n) = -6n + 32

T(10) = -6(10) + 32

T(10) = -60+32

T(10) = -28

User Prashant Pokhriyal
by
5.5k points